Ethics of Blockchain by Design: Guiding a Responsible Future for Healthcare Innovation - Muthu Ramachandran (Blockchain in Healthcare Today)
The rapid evolution of blockchain technology within healthcare presents unparalleled opportunities for advancements, including enhanced patient data security, decentralized systems for trustless operations, and transparent supply chain management. However, as blockchain reshapes the healthcare landscape, it demands a robust ethical framework that guides its design and implementation. "Ethics of Blockchain by Design" emphasizes embedding ethical principles at the heart of blockchain innovation, fostering public trust, equity, and long-term societal benefits. This paper also proposes a set of best practices guidelines on ethics of blockchain by design.